2020
DOI: 10.3390/cancers12113082
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Causal Relationship between Childhood Obesity and Acute Lymphoblastic Leukemia? A Review

Abstract: Childhood obesity is a growing epidemic with numerous global health implications. Over the past few years, novel insights have emerged about the contribution of adult obesity to cancer risk, but the evidence base is far more limited in children. While pediatric patients with acute lymphoblastic leukemia (ALL) are at risk of obesity, it is unclear if there are potential causal mechanisms by which obesity leads to ALL development. This review explores the endocrine, metabolic and immune dysregulation triggered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 179 publications
(206 reference statements)
1
11
0
5
Order By: Relevance
“…We found a statistically significant 7% increased risk of childhood leukemia for every 5-unit increase in prepregnancy BMI. Obesity has been repeatedly linked to leukemia risk in adult populations ( 65-67 ), but recent research has identified links between childhood obesity and childhood leukemia ( 68-71 ). Our own research has demonstrated a statistically significant association between childhood obesity and ALL risk among 4726 pediatric leukemia cases ( 71 ), suggesting early obesity exposure may propagate pediatric leukemia risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a statistically significant 7% increased risk of childhood leukemia for every 5-unit increase in prepregnancy BMI. Obesity has been repeatedly linked to leukemia risk in adult populations ( 65-67 ), but recent research has identified links between childhood obesity and childhood leukemia ( 68-71 ). Our own research has demonstrated a statistically significant association between childhood obesity and ALL risk among 4726 pediatric leukemia cases ( 71 ), suggesting early obesity exposure may propagate pediatric leukemia risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our own research has demonstrated a statistically significant association between childhood obesity and ALL risk among 4726 pediatric leukemia cases ( 71 ), suggesting early obesity exposure may propagate pediatric leukemia risk. Obesity may specifically promote leukemogenesis via several mechanisms, including altered adipokine secretion ( 68 ), decreased circulating adiponectin ( 72 ), and increased leptin bioavailability ( 73 , 74 ). Additionally, as obesity heritability is estimated to be 0.85-0.9 ( 75 , 76 ), obese mothers are more likely to have obese children, thus increasing leukemogenesis risk; however, with our data, there was no way to determine leukemia risk attributable to obesity genomics.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely related to the fact that if a person is obese as a child, they also tend to be obese as an adult. Increased BMI as a teen was associated with a higher risk for leukemia (OR = 1.32, 95% CI 1.15-1.53) [51,52], Hodgkin's disease (HR = 1.25, 95% CI 1.13-1.37) [49,53], and colon cancer (39% increase in men and 19% increase in women) [54].…”
Section: Obesity and Cancer Developmentmentioning
confidence: 99%
“…The articles accepted into this series focus on liver [ 4 , 5 , 6 ], uterine [ 7 ], skin [ 8 ], breast [ 9 , 10 , 11 ], prostate [ 12 ], colon [ 13 , 14 ], pancreatic [ 15 ], and acute lymphoblastic leukemia cancers [ 16 ], with a general overview of the potential impacts of obesity-related changes in host metabolism on cancer development and/or progression [ 17 ].…”
mentioning
confidence: 99%
“…Excess body mass is linked to paediatric acute lymphoblastic leukemia (ALL), but little is known about the causal role of excess weight. In this edition, Dushnicky and colleagues review the potential effects of obesity on ALL risk in the context of endocrine, metabolic and immune dysregulation [ 16 ].…”
mentioning
confidence: 99%